The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1007/s12011-011-9033-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Copper on Proliferation and Autocrine Secretion of Insulin-Like Growth Factor-1 (IGF-1) and IGF-Binding Protein-3 (IGFBP-3) in Chondrocytes from Newborn Pigs In Vitro

Abstract: Chondrocytes from the lateral trochlear ridge of the distal femur taken from 1-day-old piglets were cultured in medium supplemented with 0, 7.8, 15.6, 31.2, and 62.5 μmol/L copper. Insulin-like growth factor-1 (IGF-1) and IGF-binding protein 3 (IGFBP-3) levels in culture medium were determined by radioimmunoassay. DNA synthesis in chondrocytes was measured by tritiated thymidine ((3)H-TdR) incorporation. Proliferation-promoting activity and incorporation of (3)H-TdR in chondrocytes were increased in all cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 36 publications
(28 reference statements)
2
9
0
Order By: Relevance
“…Copper deficiency in feeds and hence in animals would damage the synthesis of cartilage [19,20]. While there were few reports about the effect of copper on chondrocyte differentiation and function, our present research showed that copper can promote the proliferentiation of chondrocytes and the synthesis of cartilage matrix, affecting chondrocyte function [15,21].…”
Section: Discussionmentioning
confidence: 51%
“…Copper deficiency in feeds and hence in animals would damage the synthesis of cartilage [19,20]. While there were few reports about the effect of copper on chondrocyte differentiation and function, our present research showed that copper can promote the proliferentiation of chondrocytes and the synthesis of cartilage matrix, affecting chondrocyte function [15,21].…”
Section: Discussionmentioning
confidence: 51%
“…Under normal circumstances, IGFBP-3 is the main carrier of circulating IGF-1, due to its high affinity. In an in vitro study, it was observed that copper supplementation in a culture medium containing 15% fetal calf serum (FCS) could promote the autocrine secretion of IGF-1 and IGFBP-3 and stimulate chondrocyte proliferation [58]. Furthermore, an animal study, which was carried out in 60 weanling pigs, concluded that the effects of Cu in their diet to supplement their growth was related to the increased serum levels induced by Cu.…”
Section: Serum Cu Levelsmentioning
confidence: 99%
“…IGF-1 can promote mammalian cell proliferation and is conducive to the growth of organisms (20,22,23). In mammals, the combination of IGF-1 and IGF-1R initiates a downstream signal transduction pathway, activating a transcription factor by transducing the extracellular signals into the nucleus.…”
Section: Discussionmentioning
confidence: 99%